2021
DOI: 10.21873/invivo.12533
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of High-flow Nasal Cannula (HFNC) and Conventional Oxygen Therapy in Obese Patients Undergoing Cardiac Surgery: A Systematic Review and Meta-analysis

Abstract: 2521Abstract. Background/Aim: High-flow nasal cannula (HFNC), a new method for postoperative oxygenation, has increasingly received attention during postoperative care. However, its importance for obese patients undergoing cardiac surgery remains controversial. This systematic review and meta-analysis compared and evaluated HFNC and conventional oxygen therapy (COT) in this patient group. Materials and Methods: Literature was retrieved by searching eight public databases. Randomized controlled trials (RCTs) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
(50 reference statements)
2
10
0
Order By: Relevance
“…Despite the recommendation of oxygen supplementation in patients at high risk of postoperative atelectasis 43 , we found that the use of HFNO was unable to improve oxygenation parameters in patients with obesity both during the periprocedural period and at three hours after surgery. Consistent with our findings, another meta-analysis investigating patients with obesity undergoing cardiac surgery demonstrated no significant improvements in atelectasis score, dyspnea score, PaO 2 /FiO 2 ratio, and reintubation rate in patients receiving HFNO compared with those undergoing COT 44 . The lack of benefits of HFNO in patients with obesity during the postoperative period underscores the need for timely intervention (e.g., reintubation) in case of respiratory distress after tracheal extubation.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the recommendation of oxygen supplementation in patients at high risk of postoperative atelectasis 43 , we found that the use of HFNO was unable to improve oxygenation parameters in patients with obesity both during the periprocedural period and at three hours after surgery. Consistent with our findings, another meta-analysis investigating patients with obesity undergoing cardiac surgery demonstrated no significant improvements in atelectasis score, dyspnea score, PaO 2 /FiO 2 ratio, and reintubation rate in patients receiving HFNO compared with those undergoing COT 44 . The lack of benefits of HFNO in patients with obesity during the postoperative period underscores the need for timely intervention (e.g., reintubation) in case of respiratory distress after tracheal extubation.…”
Section: Discussionsupporting
confidence: 90%
“…[16] In surgical discipline, HFNC can maintain patients' oxygenation in cardiac surgery. [17] There are some limitations of our study. First of all, the retrospective study design inevitably inherited some select bias.…”
Section: Discussionmentioning
confidence: 91%
“…Hung's study showed HFNC might prolong the safe apnea time, but did not improve oxygenation compared to COT or NIV in obese patients during the peri- and postprocedural period [ 7 ]. Another study involving 3 trials also showed that there was no significant advantages of improving oxygenation in HFNC compared to the COT group in obese patients who underwent cardiac surgery [ 25 ]. Nevertheless, due to limited trials being included in previous studies, the conclusion might be controversial in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analyses assessing the e cacy of HFNC in varied clinical scenarios have been published, including patients with acute respiratory failure, COPD, obesity, and patients with planned extubation in ICU [7,[24][25][26][27]. Of these studies, only two studies explored the application of HFNC in obese patients [7,25].…”
Section: Comparison With Previous Meta-analysesmentioning
confidence: 99%
See 1 more Smart Citation